Social media issues embedded in broadcasting: Malaysian experience - Ramachandran Ponnan; Mohd. Nor Shahizan Ali (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
This article provides an overview of the broadcasting industry in Malaysia. Next, it explores the social media environment and the different issues experienced by young social media users as opposed to issues found in web broadcasting, as mainstream broadcasters’ attempt to host social media generated content to achieve greater audience reach and popularity. Then the chapter discusses how broadcasters are managing these issues. The issues are analysed using the business analysis tool PESTEL and are presented in two folds. One as they are experienced by social media users and the other as experienced by conventional broadcasters who also broadcast their content through the web. The significance of the issues here is in the Malaysian context as it seems to be related to the nature of social media users, their lack of affinity to hard copy books, periodicals or printed materials, their affection to the possibilities the web and social media offers. How broadcasters are managing the issues at their end takes into consideration the cultural, legal and social context of the Malaysian society.